ALGYSH (GOODWILL) IN THE FOLKLORE AND LITERATURE OF KARACHAIS AND BALKARS: SPECIFICS OF GENRE, TAXONOMY, POETICS - Zh. M. LOKYAEVA; F. T. UZDENOVA (Кавказология, 2021)
The article is devoted to a comprehensive study of the algysh (goodwill) genre, which is actively functioning in the traditional verbal culture of the Karachais and Balkars. Based on the analysis of folklore texts and literary works, the tаxonomy of goodwill is presented, taking into account the specifics of recreational-vital practices and linguo-stylistic characteristics; the main used algysh models are noted: in connection with marriage, birth of a child, festive events, loss (condolence), etc.; the features of the etiquette speech genre of goodwill, the degree of its study, the communicative role, the poetics of linguistic embodiment are considered; special attention is paid to the representation of the form actively used in modern national literature – stylization under the algysh. A synchronous approach to the problem is a study of definitions, associated with the definition of the psycho-emotional background due to ethnicity, cognitive-epistemological processes, grammatical linguistic structures that influence the formation of the national picture of the world. Research methods: structural-descriptive, historical-typological, epistemological.